Application of N-15 Technique for Quantification of N-Fertilizer and N-Soil Uptake in Difference Maize Varieties. - Kasim, Nurlina (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
A pot study has been carried out, where thetreatments were N-fertilizers (N-F) : F0 = without N-fertilizer (F), F1 = 100% anorganic NF/ urea, F2 = 100% organic N-F, and 50% anorganic + 50% organic N-F and three maize varieties namely, var. Anoman (A), var. Lamuru (L) and var. Sukmaraga (S). An Anova was implemented to observe any difference among the treatments and their interaction (N x F) for each parameter. The parameters applied were, percentage (%) of N-F, N-soil (N-S) and N- total (N-to) the N-F, N-S, N-to uptake (mg N), and dry weight (g S for all three plant parts (stem, leaves, panicles) and the whole plant (stem + leaves + panicles). Data showed that for the percentage (%), total : N uptake, dry weight, the highest values was for F1 compared to F0, F1, F2.. Whenever differents were found in treatment and interaction ( VxF) by the parameters, it shown by the ANOVA that this was mainly due to the F treatment. The data also show that N-S uptake was much higher than the N-F uptake. It was found that although urea/anorganic fertilizer (F1) was found to give the highest values for nearly all the parameters, it used by plant expressed in percentage (%) was quite low, especially shown for the whole plant.